Cutaneous metastasis of rectal carcinoma: a rare phenomenon with poor prognosis - Paudel, Vikash; Gautam, Asmita; Suman, Abhishek; Amatya, Amit; Gyawali, Madhu; Kafle, Monique; Maharjan, Sabina; Pokhrel, Sharon; Kayastha, Bhaskar Mohan Meher (Journal of Patan Academy of Health Sciences, 2025)
Cutaneous metastasis from colorectal carcinoma is an uncommon clinical finding. It typically signifies widespread disseminated disease and is associated with a very poor prognosis. A 75-year-old male presented with multiple, progressively increasing, painful genital lesions. His history was significant for rectal adenocarcinoma. Cutaneous examination revealed multiple tender, erythematous, and skin-colored papules and nodules on the scrotum and perineal area. A skin biopsy confirmed the diagnosis of metastatic adenocarcinoma with dermal infiltration of atypical cells arranged in a glandular pattern. This case highlights the importance of considering metastatic disease in any patient with a history of malignancy who presents with new cutaneous lesions. Such metastases often appear years after the primary diagnosis and indicate disease progression, necessitating a thorough evaluation and a shift to palliative management strategies.